2022
DOI: 10.1017/s0033291722003440
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and psychotic-like experiences in young people: a systematic review and meta-analysis

Abstract: This study aimed to systematically review and synthesise the available evidence on the prevalence and associations between psychotic-like experiences (PLEs) and substance use in children and adolescents aged ⩽17 years, prior to the typical age of development of prodromal symptoms of psychosis. As substance use has been associated with earlier age of psychosis onset and more severe illness, identifying risk processes in the premorbid phase of the illness may offer opportunities to prevent the development of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
(127 reference statements)
1
3
0
Order By: Relevance
“…The age of initiation of drug use is also a variable that significantly modulates the risk of developing prodromal symptoms, but also influences higher distress scores. This has also been confirmed in other reports hypothesizing that younger individuals among psychoactive substance users may represent a subclinical risk group for psychosis [27]. Effective addiction prevention and psychoeducation among young people about the relationship between substance use and the possible occurrence of prodromal symptoms is a key element in the prevention of psychotic disorders.…”
Section: Discussionsupporting
confidence: 72%
“…The age of initiation of drug use is also a variable that significantly modulates the risk of developing prodromal symptoms, but also influences higher distress scores. This has also been confirmed in other reports hypothesizing that younger individuals among psychoactive substance users may represent a subclinical risk group for psychosis [27]. Effective addiction prevention and psychoeducation among young people about the relationship between substance use and the possible occurrence of prodromal symptoms is a key element in the prevention of psychotic disorders.…”
Section: Discussionsupporting
confidence: 72%
“…Considering the correlation between PLEs and psychoactive substances (as outlined in the meta-analysis by Matheson et al [ 83 ]), we also gathered information regarding their usage among the subjects. It was revealed that the most commonly used substance was alcohol (88%), followed by marijuana or hashish (45.5%).…”
Section: Methodsmentioning
confidence: 99%
“…The 6-item paranoid ideation subscale and the 10-item psychoticism subscale of the BSI [107,108] were used to measure participants' PEs. The "paranoid ideation" and "psychoticism" dimensions have been largely used to assess PEs in the general population (e.g., [30,[109][110][111][112][113][114][115][116]), and have been included as measurement tools of PEs in previous meta-analyses (e.g., [117,118]). The paranoid ideation subscale detects paranoia symptoms that involve delusion of reference and suspicion; while the psychoticism subscale identifies psychotic symptoms such as auditory hallucination, experience of thought insertion, thought control, and thought being revealed.…”
Section: The Bsimentioning
confidence: 99%